Integration of agricultural technology in the development of horticulture-based agro-tourism in Enrekang Regency - Firda Rahmayanti; Risaldi Ismail; Farid Asfari Rahman; Titing Kartika (Journal of Rural Tourism, 2024)
Purpose - The purpose of this research is to explore the untapped potential of agrotourism in Dante Mararih Hamlet, Tangru Village, Malua District, Enrekang Regency, South Sulawesi, and assess public awareness regarding the importance of its development. Methodology/Design/Approach - A qualitative approach was used, combining observation, interviews, and documentation to gather data on the potential of agrotourism in the area and public awareness of its development.Finding - The study found that Dante Mararih Hamlet has significant potential for agrotourism, driven by its horticultural resources, cultivation activities, natural beauty, and the quality of the local community. However, public awareness about agrotourism is still low, and there is a need to align perceptions to fully realize the potential. The development of agrotourism will require attention to various factors, including human resources, infrastructure, location, traditional agriculture characteristics, and agro-industry.Originality/Value - This research emphasizes the importance of raising public awareness and aligning perceptions to optimize agrotourism potential. It provides practical insights into the factors necessary for successful agrotourism development, which could positively impact the economy of Dante Mararih Hamlet.